O ensino de língua portuguesa na perspectiva do professor: que gramática devemos ensinar? - Santos, Domingas Ferreira dos (Universidade Federal do Tocantins, 2022)
The goal of this article is to investigate the contextualized teaching of the language going from the representation of teachers from the municipal network, from a city, from the interior, and from the state of Tocantins about working with grammar in the classroom. For this purpose, was created an application of a questionnaire with a group of four teachers of fundamental teaching who supervise the discipline of the Portuguese language from a public school in the municipality of Porto Nacional, TO. Thus, to reflect and analyze the teachers’ findings about the teaching of grammar, we use as theoretical back up: Geraldi (1997), Travaglia (2009), Mendonça (2006), Antunes (2014), Batista-Santos; Teles (2018) among others. Through a quantitative-interpretive analysis, it was verified that there still exists a predominance of a teaching practice of normative grammar, evidencing the triad: Conceptualization, classifications and mechanical exercises without the possibility of reflection about the effects of meanings that this type of words plays in the text. However, even with such evidence it was noted in the teachers’ representations the need of change in the pedagogical practices for the teaching of grammar, considering the context of use as well as a productive work (use-reflection-use) of reflection and critical standpoints.